MicroRNA-524 inhibits the progress of glioma via the direct targeting of NCF2 - Xu, Tuoye (Am J Transl Res, 2019)
In recent years, a large amount of research has reported that microRNA (miRNA) dysregulation is closely related to glioma progression. miR-524, a member of the miRNA family, has been confirmed to be involved in many human diseases, including glioma. However, the role and molecular mechanism of miR-524 in glioma have not been clarified. In our study, we showed that miR-524 expression was significantly decreased in glioma and was associated with glioma recurrence. Next, we performed a series of assays and confirmed that the upregulation of miR-524 suppressed glucose uptake, proliferation, migration and invasion in glioma cell lines. Then, through bioinformatics software and a dual luciferase assay, we demonstrated that NCF2 was a target gene of miR-524. In addition, we found that NCF2 reintroduction restored the inhibitor effect of miR-524 on glioma progression. These results elucidate the mechanism of miR-524 in glioma development and provide a potential therapeutic strategy for glioma patients.